The Role of Consumer Satisfaction as an Intervening Variable In Mediating The Relationship Between Service Quality and Consumer Loyalty in Shopeefood Application Users in Semarang City - Najiyah, Ainun; Firdaus, Firdaus (Economics and Business International Conference Proceeding, 2024)
This research aims to determine and test the role of consumer satisfaction as an intervening variable in mediating the relationship between service quality and consumer loyalty among ShopeeFood users in Semarang City. The research population is ShopeeFood application users who live in Semarang City. The sampling technique uses a probability sampling technique with a purposive sampling method by distributing questionnaires via Google Form which is distributed via social media. The sample used in the research was 141 respondents and the data was processed using SMART-PLS 3.0. The results of the research show that (1) Service quality has a positive and significant effect on consumer loyalty. (2) service quality has a positive and significant effect on consumer satisfaction. (3) Consumer satisfaction has a positive and significant effect on consumer loyalty. (4) Consumer satisfaction mediates the relationship between service quality and consumer loyalty. For further research, it is recommended to add variations to the independent variables used and take samples in different cities so that the results can be compared with this research.